Influence of DER and PER on Finance Performance in Financial Company Listed Indonesian Stock Exchange - Mohamad Syam Amirrullah; Sri Marhaeni Salsiyah; Achmad - Zaenuddin (Politeknik Negeri Semarang, 2022)
This study aims to determine the effect of DER and PER on Finance Performance in financial company listed Indonesian stock exchange. This research is classified as quantitative descriptive research with data periode 2019 until 2021. The data in this study use multiple linear regression analysis techniques, R2 test and t test. The results of the study show that: 1. DER variable shows that there is a negative significant effect on the variable Finance Performance. 2. The PER shows that there is negative and unsignificant influence on the variables of Finance Performance. Based on the calculation of the multiple linear regression analysis model Y= 5.608 – 0.528X1 – 0.050X2 + E. So it can be said that Y as finance performance, X1 as DER, X2 as PER